2020
DOI: 10.1371/journal.pone.0229185
|View full text |Cite
|
Sign up to set email alerts
|

Contrast versus identity encoding in the face image follow distinct orientation selectivity profiles

Abstract: Orientation selectivity is a fundamental property of primary visual encoding. High-level processing stages also show some form of orientation dependence, with face identification preferentially relying on horizontally-oriented information. How high-level orientation tuning emerges from primary orientation biases is unclear. In the same group of participants, we derived the orientation selectivity profile at primary and high-level visual processing stages using a contrast detection and an identity matching task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
(122 reference statements)
2
7
0
Order By: Relevance
“…Meanwhile, in our second experiment, we find horizontal selectivity commensurate with previous studies 31 , 32 , 34 , 35 , as suggested by improved model fits when adding orientation as a factor (Figs. 2 , 3 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, in our second experiment, we find horizontal selectivity commensurate with previous studies 31 , 32 , 34 , 35 , as suggested by improved model fits when adding orientation as a factor (Figs. 2 , 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the first, we test whether consistent exploitation of retinally available spatial frequency information (across simulated viewing distances) 27 during unfamiliar face matching differentiates SRs from a sample of control observers. In the second, testing the same two groups of observers, we assess whether such (potential) differences extend to increased consistency in horizontal versus vertical spatial frequency structure as shown in previous research 31 35 .…”
Section: Introductionmentioning
confidence: 91%
“…In our second experiment, we find horizontal selectivity commensurate with previous studies (Goffaux, Poncin & Schiltz, 2015;Goffaux & Greenwood, 2016;Pachai et al, 2017;Jacobs et al, 2020). Specifically, horizontal spatial frequency information is more diagnostic for facial identity matching than vertical, among both groups of observers.…”
Section: Discussionsupporting
confidence: 89%
“…In the first, we test whether consistent exploitation of retinally available spatial frequency information (as in Figure 1a) during unfamiliar face matching differentiates SRs from a sample of normal observers as controls (See Method section for details). In the second, testing the same two groups of observers, we assess whether such (potential) differences extend to greater selectivity for horizontal spatial frequency structure as shown in previous research (Goffaux, Poncin & Schiltz, 2015;Taubert et al, 2016;Goffaux & Greenwood, 2016;Jacobs et al, 2020) (See Method section for details).…”
Section: Introductionmentioning
confidence: 95%
“…Since manipulations in the Fourier domain operate on the whole image (face and background), the presence of a uniform background artificially increases the LSF energy of scrambled images. In order to minimise contamination of the phase-scrambled image by its originally uniform background, we employed an iterative phase scrambling procedure (as in Jacobs et al, 2020; Petras et al, 2021; Petras et al, 2019; see Figure 1a). Iterative scrambling involves first generating a phase scrambled version of the face image, then superimposing the original face back onto the scrambled image, scrambling this new image again, and repeating the procedure several times (for all our scrambled stimuli, 500 iterations were used).…”
Section: Methodsmentioning
confidence: 99%